2022
DOI: 10.3390/pharmaceutics14112307
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Evaluation of a Novel Organic Anion Transporter 1/3 CRISPR/Cas9 Double-Knockout Rat Model

Abstract: Background: Organic anion transporter 1 (OAT1) and OAT3 have an overlapping spectrum of substrates such that one can exert a compensatory effect when the other is dysfunctional. As a result, the knockout of either OAT1 or OAT3 is not reflected in a change in the excretion of organic anionic substrates. To date, only the mOAT1 and mOAT3 individual knockout mouse models have been available. Methods: In this study, we successfully generated a Slc22a6/Slc22a8 double-knockout (KO) rat model using CRISPR/Cas9 techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In rats with a CRISPR/Cas9-mediated double KO of OAT1 (Slc22a6) and OAT3 (Slc22a8), renal dysfunction was observed in 4-week-old rats, but this was ameliorated by 7 weeks ( 57 ). This was apparently due to a compensatory increase in renal SLCO4C1 expression by 7 weeks ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats with a CRISPR/Cas9-mediated double KO of OAT1 (Slc22a6) and OAT3 (Slc22a8), renal dysfunction was observed in 4-week-old rats, but this was ameliorated by 7 weeks ( 57 ). This was apparently due to a compensatory increase in renal SLCO4C1 expression by 7 weeks ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…In rats with a CRISPR/Cas9-mediated double KO of OAT1 (Slc22a6) and OAT3 (Slc22a8), renal dysfunction was observed in 4-week-old rats, but this was ameliorated by 7 weeks ( 57 ). This was apparently due to a compensatory increase in renal SLCO4C1 expression by 7 weeks ( 57 ). Previous work has shown that overexpression of the OATP transporter, SLCO4C1, has a protective effect on 5/6 nephrectomy rats modeling CKD by reducing systemic uremic toxin levels ( 58 ).…”
Section: Discussionmentioning
confidence: 99%